Isolation and characterization of CNC from waste maize cob available in Bangladesh as a potential candidate for the fabrication of multifunctional bio-nanocomposites: A new approach - Shamim Dewan; Md. Mahmudur Rahman; Md. Ismail Hossain; Bijoy Chandra Ghos; M Mohinur Rahman Rabby; Md. Abdul Gafur; Md. Al-Amin; Md. Ashraful Alam (South African Journal of Chemical Engineering)
Nano-cellulose is a biodegradable polysaccharide which has multifunctional uses due to its fascinating properties (i.e., antibacterial, antifungal, anticarcinogenic activity) in wastewater treatment, drug design, food packaging, etc. CNC usually extracted from primary plant (such as jute, hemp, flax, cotton, etc.) which has other significant uses (for example preparation of yarn, rope, tissue paper, etc.). To reduce the pressure on primary plant the use of waste biomass of secondary plant could be an effective and economic route of CNC isolation. In this study a series of chemical treatment i.e. scouring (5% soap solution), alkali treatment (16% NaOH solution), bleaching (2% NaClO2 and 2% Na2S2O5 solution at pH = 4.0), acid hydrolysis (60% H2SO4) was conducted to isolate CNC from the waste maize cob. Characterization of the specimens were conducted by FTIR-ATR (Fourier Transform Infrared-Attenuated Total Reflection), FESEM (Field Emission Scanning Electron Microscopy), XRD (X-ray Diffraction), EDX (Energy Dispersive X-ray), DLS (Dynamic Light Scattering), Thermal analysis (TGA/DTG/DTA), and Zeta potential analysis. Different functional groups (>C=O, C≡C, C-O-C, C-O, -OH, etc.) were identified by FTIR-ATR. Crystal structure, crystallite size, and crystallinity index of CNC (around 84.63±0.03%) were observed by XRD analysis. Produced CNC showed enhanced thermal stabilities in TGA/DTG/DTA curves (about 40% residual mass at 600 °C) with the appearance of a peculiar 2D honey comb like void surface microstructure in FESEM micrographs and the surface charge (around -7.09mV) was measured by zeta potential. The newly produced CNC was perfectly nano sized (around 100 nm according to DLS analysis and FESEM micrograph). Hence, this newly produced CNC would be beneficially used to fabricate bio-nanocomposites for potential applications in various sectors such as biomedical, engineering, and industrial wastewater treatment as an appropriate substitute of the unsafe fossil based synthetic ones to develop legitimate environment.